The phosphoinositide 3-kinase inhibitor ZSTK474 increases the susceptibility of osteosarcoma cells to oncolytic vesicular stomatitis virus VSVΔ51 via aggravating endoplasmic reticulum stress. Issue 2 (20th December 2021) - Jiang, Jinqiong; Wang, Weida; Xiang, Weineng; Jiang, Lin; Zhou, Qian
ABSTRACT: Blockage of phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) signal pathway is effective to increase the cytotoxic effects of oncolytic virus on cancer cells, but the detailed mechanisms are still largely unknown. Based on this, the present study managed to investigate the anti-tumor effects of PI3K inhibitor ZSTK474 and oncolytic vesicular stomatitis virus VSVΔ51 combination treatments on osteosarcoma (OS) in vitro and in vivo . Specifically, ZSTK474 aggravated the inhibiting effects of VSVΔ51 on osteosarcoma development by triggering endoplasmic reticulum (ER)-stress mediated apoptotic cell death. Mechanistically, either ZSTK474 or VSVΔ51 alone had limited effects on cell viability in osteosarcoma cells, while ZSTK474 and VSVΔ51 combination treatments significantly induced osteosarcoma cell apoptosis. Interestingly, VSVΔ51 increased the expression levels of IRE1α and p-PERK to initiate ER stress in osteosarcoma cells, which were aggravated by co-treating cells with ZSTK474. Next, the promoting effects of ZSTK474-VSVΔ51 combined treatment on osteosarcoma cell death were abrogated by the ER-stress inhibitor 4-phenyl butyric acid (4-PBA), indicating that ZSTK474 enhanced the cytotoxic effects of VSVΔ51 on osteosarcoma cells in an ER-stress dependent manner. Finally, the xenograft tumor-bearing mice models were established, and the results showed that ZSTK474-VSVΔ51 combined treatment synergistically hindered tumorigenesis of osteosarcoma cells in vivo . Taken together, our data suggested that ZSTK474 was a novel agent to enhance the cytotoxic effects of VSVΔ51 on osteosarcoma by aggravating ER-stress, and the present study might provide alternative therapy treatments for osteosarcoma in clinic.